Sleep quality and quantity of international rugby sevens players during pre-season - Leduc, C.; Jones, B.; Robineau, J.; Piscione, J.; Lacome, M. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to investigate the influence of training load on objective and subjective sleep measures among elite rugby sevens players during pre-season. Nine international male rugby sevens players participated in this study. Actigraphic and subjective sleep assessment were performed on a daily basis to measure sleep parameters. Training load was measured during the entire pre-season period, and sleep data from the highest and lowest training load week were used in the analysis through magnitude-based inferences. During the highest training load, likely to possibly small, moderate decreases in time in bed (effect sizes; ±90% confidence limits: -0.42; ±0.44 for session rating of perceived exertion [sRPE], -0.69; ±0.71 for total distance covered [TDC]) and total sleep time (-0.20; ±0.37 for sRPE, -0.23; ±0.35 for TDC) were found. Possibly small (-0.21; ±0.35 for high-speed distance, -0.52; ±0.73 for acceleration/deceleration [A/D]) and likely moderate (-074; ±0.67 for TDC) decreases were observed in subjective sleep quality. Possibly small to very likely moderate changes in sleep schedule were observed. Sleep quantity and subjective quality seem to be deteriorated during higher loads of training. This study highlights the necessity to monitor and improve sleep among elite rugby sevens players, especially for the intense period of training.